Emotional Dissonance, Mental Health Complaints, and Sickness Absence Among Health- and Social Workers. The Moderating Role of Self-Efficacy - Indregard, Anne-Marthe R.; Knardahl, Stein; Nielsen, Morten B. (Frontiers in Psychology, 2018)
Health- and social workers are frequently exposed to emotionally demanding work situations that requires emotion regulation. Studies have demonstrated a direct relationship between emotion regulation and health complaints and sickness absence. In order to prevent health complaints and to reduce sickness absence among health- and social workers, there is need for greater attention to mechanisms explaining when and how emotionally demanding work situations are related to employee health and sickness absence. The overarching aim of this study was therefore to examine the moderating role of generalized self-efficacy on the association between emotional dissonance, employee health (mental distress and exhaustion), and registry based sickness absence. The sample consisted of 937 health- and social workers. Data on emotional dissonance, self-efficacy, exhaustion, and mental distress was collected through questionnaires, whereas official registry data were used to assess sickness absence. A two-step Hierarchical regression analysis showed that emotional dissonance was significantly associated with exhaustion, mental distress, and sickness absence, after adjusting for sex, age, and occupation. Interaction analyses with simple slope tests found that self-efficacy moderated the association between emotional dissonance and both exhaustion and mental distress, but not the association with sickness absence. This study shows that health- and social workers who frequently experience emotional dissonance report higher levels of exhaustion and mental distress, and have a higher risk of medically certified sickness absence. Further, health- and social workers with lower self-efficacy beliefs are apparently more sensitive to the degree of emotional dissonance and experienced higher levels of exhaustion and mental distress.